2016
DOI: 10.1007/s12289-016-1320-9
|View full text |Cite
|
Sign up to set email alerts
|

Finite element simulations of stretch-blow moulding with experimental validation over a broad process window

Abstract: Injection stretch blow moulding is a wellestablished method of forming thin-walled containers and has been extensively researched for numerous years. This paper is concerned with validating the finite element analysis of the free-stretch-blow process in an effort to progress the development of injection stretch blow moulding of poly(ethylene terephthalate). Extensive data was obtained experimentally over a wide process window accounting for material temperature and air flow rate, while capturing cavity pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…An accurate model of PET for stretch blow molding must be characterized at temperatures and strain rates typically seen in the process. Nixon et al [1] demonstrated through free-blowing preforms while monitored via high-speed video that the strain rate has an average of 40 s −1 [1], whereas it is well recognized in the industry the temperature range of interest is between 90 C and 120 C, that is, just above the T g but just below the cold crystallization temperature.…”
Section: Introductionmentioning
confidence: 99%
“…An accurate model of PET for stretch blow molding must be characterized at temperatures and strain rates typically seen in the process. Nixon et al [1] demonstrated through free-blowing preforms while monitored via high-speed video that the strain rate has an average of 40 s −1 [1], whereas it is well recognized in the industry the temperature range of interest is between 90 C and 120 C, that is, just above the T g but just below the cold crystallization temperature.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically three different preform length cases were taken under consideration preform length is a parameter that is has not been investigated before. The study also comprises the effort to ma the preform temperature as much as possible above the glass-rubber limit which is about 80°C [14]. Stretchi preform above this limit induces crystallization [14].…”
Section: Introductionmentioning
confidence: 99%
“…The study also comprises the effort to ma the preform temperature as much as possible above the glass-rubber limit which is about 80°C [14]. Stretchi preform above this limit induces crystallization [14]. Stretching may also occur during the material deform while the blown preform fills the mold cavities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations